Review Article UPDATE ON MYASTHENIA GRAVIS: UPDATE ON MYASTHENIA GRAVIS (Bombay Hospital Journal, 2022)
AbstractMyasthenia gravis is an autoimmune disease mediated by autoantibodies against various transmembrane proteins located on the post synaptic membrane. Our understanding of pathophysiology has vastly improved over the last decade, resulting in the development of individualized therapeutic options. Classification into myasthenia subgroups, depending on the antibody profile, helps to better characterize, treat, and prognosticate patients. It is quite evident that MuSK myasthenia needs early Rituximab intervention for a stable remission. Role of thymectomy, although never in doubt, was recently proven in randomized controlled trial. With the advent of monoclonal antibodies and other newer modalities, we should evolve beyond the conventional immunosuppressives, given their toxicities. Better potential options are now available to treat the refractory subgroup. Future of myasthenia treatment clearly has rosy predictions. Present review is an update on myasthenia gravis.
Keywords: Myasthenia gravis. Thymus. Autoantibodies. Treatment guidelines